Vers une justice multi-espèces : cadre théorique, enjeux et programme de recherche pour les théories et politiques environnementales - Danielle Celermajer; David Schlosberg; Lauren Rickards; Makere Stewart-Harawira; Mathias Thaler; Petra Tschakert; Blanche Verlie; Christine Winter (Développement Durable et Territoires)
This essay seeks to open a conversation about multispecies justice in environmental politics. It sets out some of the theoretical approaches, key areas of exploration, and obvious challenges that come with rethinking a core plank of liberal theory and politics. First, we discuss some of the diverse scholarly fields that have influenced the emergence of multispecies justice. We then discuss core concerns at the centre of this reconfiguration of justice – including broadening conceptions of the subject of justice and the means and processes of recognition (and misrecognition). The importance of deconstructing and decolonising the hegemony of liberal political discourse is crucial, and is part of a larger project for multispecies justice to rework a politics of knowledge and practice of political communication. Finally, we begin to explore what a commitment to multispecies justice might demand of politics and policy.